UV Map Shader Development for Fluids Simulation with Material Point Method Model - Anthony S, Christian
Fluid simulation computation is not only limited for research or industrial purpose, but can also be implemented into personal computer software. As the demand of fluid simulation is growing from research to movies and games, we need a good rendering of fluids with the most sophisticated fluid model. In this paper, we explore a shader development for a two-dimensional material-point method (MPM) based fluid simulation with fluid particle. The results from MPM is then rendered with multiple steps of GLSL program. The steps are from creating a pill geometry shader, blurring shader, and threshold shader. Performance drop between 50%-80% is observed in the implementation, with the maximum number of particles to be simulated is 75.000 particles. Finally, we found that some of the parameter for those shader affects heavily on the performance while the result is not affected that much.